2016
DOI: 10.1038/nchembio.2019
|View full text |Cite
|
Sign up to set email alerts
|

A proactive role of water molecules in acceptor recognition by protein O-fucosyltransferase 2

Abstract: Protein O-fucosyltransferase 2 (POFUT2) is an essential enzyme that fucosylates serine/threonine residues of folded thrombospondin type 1 repeats (TSRs). To date, the mechanism by which this enzyme recognizes very dissimilar TSRs remained unclear. By engineering of a fusion protein, we report the crystal structure of Caenorhabditis elegans POFUT2 (CePOFUT2) in complex with GDP and human TSR1 that suggests an inverting mechanism for fucose transfer assisted by a catalytic base, and shows that nearly half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 46 publications
15
82
0
Order By: Relevance
“…Pulse-chase experiments have shown that C-mannosylation occurs early, potentially before or during folding (13) and likely precedes O-fucosylation, which takes place on folded proteins (37,38). This hypothesis is consistent with our observation that we never see fucose on nonmannosylated peptides.…”
Section: Restitution Of Dpy19l1 -L3 and -L4 In The Triple Knockout supporting
confidence: 82%
“…Pulse-chase experiments have shown that C-mannosylation occurs early, potentially before or during folding (13) and likely precedes O-fucosylation, which takes place on folded proteins (37,38). This hypothesis is consistent with our observation that we never see fucose on nonmannosylated peptides.…”
Section: Restitution Of Dpy19l1 -L3 and -L4 In The Triple Knockout supporting
confidence: 82%
“…We confirm that at least three sites in MIC2 (S 285 , S 485 and T 546 , Figure 3) are modified by GluFuc in addition to seven sites of C-glycosylation. These O-glycosylation sites lie within the previous proposed POFUT2 consensus sequon CXX(S/T)C (11,30,31) and suggest that TgPOFUT2 has a similar substrate preference to metazoan POFUT2 enzymes. Our data demonstrates that these sites are modified to a high occupancy with few peptide species lacking the O-glycans observed in parental MIC2 preparations.…”
Section: Discussionsupporting
confidence: 77%
“…This may suggest that GalNAc-T11 is unique among the GalNAc-T isoforms in recognizing folded domains as substrates. Other glycosyltransferases initiating O-Fuc, O-Glc, and O-GlcNAc recognize small folded domains such as epidermal growth factor-like (EGF) and thrombospondin type 1 repeats (TSR) (26,36), and these domains share a design with three conserved disulphide bridges with the LA-modules (37)(38). However, in all cases the acceptor sites are located in the folded domain, while the substrate site for GalNAc-T11 is located in the short linker between the folded domains.…”
Section: Discussionmentioning
confidence: 99%